2005
DOI: 10.1182/blood-2004-04-1422
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I, NKG2D, and natural cytotoxicity receptors regulate multiple myeloma cell recognition by natural killer cells

Abstract: IntroductionNatural killer (NK) cells are cytotoxic and cytokine-producing lymphocytes, involved in the immune defense against viral infections and tumors. 1 Their homeostasis is regulated by cytokines and membrane associate receptors able to inhibit or activate cellular programs. 2 The inhibitory receptors are well characterized and described extensively in several reviews. [3][4][5] Triggering of NK cells depends largely on NK receptor member D of the lectinlike receptor family (NKG2D) and natural cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
278
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(298 citation statements)
references
References 45 publications
15
278
0
3
Order By: Relevance
“…In contrast, late-stage MM cells have a high MHC I and a low MICA expression, suggesting the emergence of NK-resistant subclones during disease progression [42]. These results are in accordance with reports describing an increase of NK-associated activation markers in early stage MM [43] and reduced NK-cell levels in untreated MM [18].…”
Section: Nk and Nkt Cellssupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, late-stage MM cells have a high MHC I and a low MICA expression, suggesting the emergence of NK-resistant subclones during disease progression [42]. These results are in accordance with reports describing an increase of NK-associated activation markers in early stage MM [43] and reduced NK-cell levels in untreated MM [18].…”
Section: Nk and Nkt Cellssupporting
confidence: 82%
“…The production of TGF-β by myeloma and stromal cells contributes to the inhibitory effects on normal B-cell proliferation and antibody secretion [41]. [12,42].…”
Section: B Cells and Humoral Immunitymentioning
confidence: 99%
“…NKG2D was reported to play an important role in the NK cell-mediated killing of MM cells (17)(18)(19), and high levels of sMICA in sera of MM patients correlate with the disease stage, strongly suggesting sMICA as an independent prognostic factor in newly diagnosed MM patients (20,21).…”
mentioning
confidence: 99%
“…4,5 NKG2DL, however, are stress-inducible and often found to be expressed on a variety of solid tumors and lymphoproliferative malignancies. [6][7][8][9][10][11][12][13][14][15] Consequently, the expression of both, the NKG2D receptor and its ligands, has a crucial role in immune defense mechanisms against tumor cells by T and NK cells: studies in mice showed that NK and CD8 T cells eliminated NKG2DL-positive tumor cells through the NKG2D receptor. 16,17 It was further shown that NKG2D protected the host from tumor initiation.…”
Section: Introductionmentioning
confidence: 99%